THEORETICAL FOUNDATIONS OF ECONOMIC GROWTH RESEARCH (ON THE EXAMPLE OF NAMANGAN REGION) (American Journal of Business Management, Economics and Banking, 2025)
Economic growth represents one of the key indicators of a country's development and plays an important role in strengthening economic stability, improving the quality of life, and addressing urgent social challenges. Regional economies (using the Namangan region as an example) are complex, multi-component systems influenced by both internal (social, economic, and cultural) and external (global and national) factors.Modern processes of globalization, digitalization, and structural economic transformation enhance the significance of the regional level within the national development system. Regional economies are becoming not only an object of state policy but also an independent source of economic growth, innovation, and social stability. Under these conditions, special attention is paid to studying the factors determining sustainable regional development and to forming effective mechanisms for managing these processes.The Namangan region occupies one of the key positions in the socio-economic structure of the Republic of Uzbekistan. The region is characterized by high agricultural potential, a developing industrial sector, active entrepreneurship, and growing investment attractiveness. At the same time, structural imbalances remain, along with the need to increase labor productivity and introduce innovative technologies. Studying the trends and specific features of the region’s economic growth makes it possible to identify priority directions of regional policy and to ensure balanced territorial development.